Wieczerza Pańska – „pamiątka” Chrystusowej męki, śmierci i zmartwychwstania jako ekspiacyjnej Ofiary „za wielu” i Ofiary Nowego Przymierza (1 Kor 11,23-27; Łk 22,19-20) - Witczyk, Henryk (The Biblical Annals, 2018)
Research on the role of oral tradition (orality) in the process of Gospel and Pauline letters composition provides a basis for the synchronic reading of the traditions on the Last Supper (Matt 26:26-29; Mark 14:22-24; Luke 22:14-14-20; 1 Cor 11:23-26). The author, taking into consideration the data contained in the mentioned textual traditions, seeks an answer to the question of what Jesus recommended to his disciples in the Cenacle by saying: “Do this in remembrance of me” (Luke 22:19; 1 Cor 11:24). The author enters into a polemic with the latest theories according to which Jesus intended to celebrate the Last Supper as a “covenant sacrifice”, precisely speaking a “feast of covenant”. Through the analysis of the formulas pronounced over bread and wine, which take into consideration the texts on the suffering and death of Jahwe’s Servant (Isa 53), the author seeks to demonstrate that Jesus applied to his death the sense of the sacrifice of expiation which also establishes the New Covenant. To interpret the formulas only in light of “covenant sacrifice/feast” means to radically diminish the meaning of the prophetic words and gestures of Jesus from the Last Supper.